Epidermal growth factor receptor and anaplastic lymphoma kinase testing and mutation prevalence in patients with advanced non‐small cell lung cancer in Switzerland: A comprehensive evaluation of real world practices. (30th May 2017) - Ess, S.M.; Herrmann, C.; Frick, H.; Krapf, M.; Cerny, T.; Jochum, W.; Früh, M.
Abstract : In order to improve outcomes, identification of the epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) genes has become crucial in advanced non‐small‐cell lung cancer (NSCLC). The aim of the present study is to analyse time trends and frequency of testing, factors affecting testing as well as prevalence of mutations in the Swiss population. We analysed EGFR and ALK testing in a cohort of patients with newly diagnosed metastasised non‐squamous NSCLC in the catchment area of the cancer registry Eastern Switzerland in the years 2008–2014. We analysed prevalence of mutations and studied clinicopathological characteristics and survival of tested and non‐tested patients and of patients with and without mutations. Among 718 patients identified, 11% (51/447) harboured an EGFR mutation in the exons 18, 19 or 21 and further 12% (31/265) showed a positive test result for ALK rearrangements. In non‐smokers the proportions of mutations were 31% and 23% respectively. Testing rates increased over time and reached 79% in 2014. We observed significantly lower testing rates and poorer survival in elderly, patients with limited life expectancy and patients treated at hospitals not involved in clinical research. Outcomes can be further improved in a considerable proportion of patients with advanced non‐squamous NSCLC.